Physiological, biochemical and molecular aspects of induced resistance in maize against Bipolaris maydis infection using a zinc-polyphenolic compound and silicon - Lata Tenesaca, Luis Felipe (2023)
Maize leaf blight (MLB), caused by the fungus Bipolaris maydis, has great potential to cause considerable losses in the growth and yield of maize. Higher foliar concentration of silicon (Si) or the use of resistance inducers may be promising alternatives for boosting maize resistance against MLB. The first study investigated the potential of using Semia® [zinc (20%) complexed with plant- derived pool of polyphenols (10%)] to boost defense reactions on maize leaves infected by B. maydis. Mycelial growth and conidia germination were reduced by the IR stimulus in vitro. The IR stimulus-sprayed plants showed reduced MLB symptoms due to less production of malondialdehyde (MDA), hydrogen peroxide (H2O2), and radical anion superoxide (O2●-) compared to control plants. During the infection by B. maydis, IR stimulus-sprayed plants showed increased concentrations of sucrose and starch and greater activities of catalase (CAT), glutathione reductase (GR), and superoxide dismutase (SOD) compared to water-sprayed plants. Less impairment on the photosynthetic apparatus [higher values for leaf gas exchange (rate of net CO 2 assimilation, stomatal conductance to water vapor, and transpiration rate) and chlorophyll a fluorescence (variable-to-maximum Chl a fluorescence ratio, photochemical yield, and yield for dissipation by down-regulation) parameters] along with preserved pool of chlorophyll a+b and carotenoids were noticed for infected and IR stimulus-sprayed plants compared to infected plants from the control treatment. Defense-related genes (IGL, CHS02, PR1, PAL3, LOX3, CHI, and GLU) were up-regulated for IR stimulus-sprayed plants compared to control plants infected by B. maydis. These findings highlight the potential of using this IR stimulus for MLB management. In the second study, we investigated whether maize plants with higher foliar silicon (Si) concentration can be more resistant against MLB was investigated in this study. The +Si plants showed reduced MLB symptoms (smaller lesions and lower disease severity) due to higher foliar Si concentration and less production of MDA, H2O2, and O2●- compared to -Si plants. Higher values for leaf gas exchange and chlorophyll a fluorescence parameters along with preserved pool of chlorophyll a+b and carotenoids were noticed for infected +Si plants compared to infected -Si plants. Activities of defense (chitinase, β-1,3-glucanase, phenylalanine ammonia-lyase, polyphenoloxidase, peroxidase, and lipoxygenase) and antioxidative (APX, CAT, SOD, and GR) enzymes were higher for infected +Si plants compared to infected -Si plants. Collectively, this study highlights the importance of using Si to boost the resistance of maize plants against MLB considering the more operative defense reactions and the robustness of the antioxidative metabolism along with the preservation of the photosynthetic apparatus. Keywords: Antioxidative metabolism. Foliar disease. Host defense responses. Induced resistance. Photosynthesis.